Customer Loyalty Improvement of PT Federal International Finance Danastra Bogor Area - Risda Novita Sari; Mutiara Rofingi; Purwadi Purwadi; Syafira Rindiyani; Denny Rudiyono; Adam Hidayah; Wahid Akbar Basudani (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2024)
Online loans (pinjol) are increasingly being used by the public, especially during the Covid-19 pandemic where many households are experiencing extraordinary economic pressure. The Financial Services Authority (OJK) provides information regarding the amount of loan disbursements through loan organizing institutions or commonly known as online loan providers (pinjol) in Indonesia touched Rp 20.53 trillion in August 2023. PT Federal International Finance Danastra is an application engaged in multipurpose financing such as working capital, wedding capital, education financing and many other needs to support life. The purpose of the study was to determine how much influence service quality, brand image and customer trust have on customer satisfaction and its impact on customer loyalty at PT. Federal International Finance Danastra, this research uses quantitative analysis methods using SPSS 26 software and the sampling method uses simple random sampling with a sample size of 270 respondents using the Slovin model. Through this research analysis, it is known that the factors of service quality, brand image, consumer trust and consumer satisfaction have a strong and significant influence on consumer loyalty PT. Federal International Finance Danastra.